Actitudes hacia el Idioma Inglés y el nivel de aprendizaje en Estudiantes del segundo grado de educación secundaria del área de Idioma Extranjero - Inglés, de la institución educativa "Juan Jiménez Pimentel" del distrito de Tarapoto, en el año 2008 - Del Aguila Morey, Marco Anthony (2009)
The present investigation entitled: "Altitudes towards the English language and the level of students' learning in the Second Year of Secondary Education in the area of foreign language - English, in the Educational institution "JUAN JIMENEZ PIMENTEL" in Tarapoto District, during the academic year 2008", had as an objective to determine the relationship between altitudes towards the English language and the level of students' learning in the Second year of Secondary Education in the area of foreign language - English, in the Educational institution JUAN JIMENEZ PIMENTEL in Tarapoto District, during the academic year 2008. For that the hypothesis, that !he altitudes towards the English language is related significantly to the level of students' learning in the Second Year of Secondary Education in the area of foreign language - English, in the Educational institution JUAN JIMENEZ PIMENTEL" in Tarapoto District, during the academic year 2008, has been proved. This investigation of transactional correlation design was developed with a universe sample of 277 students, to whom a Likert Scale have been administered to measure altitudes, a test of reading comprehension and a test of text production in the English language. The data collected were processed using the Pearson Correlation Coefficient, through which has been determined that the altitudes towards the English language is related significantly to the level of students' learning in the Second Year of Secondary Education in the area of foreign language - English, in the Educational institution "JUAN JIMENEZ PIMENTEL," demonstrated with the Pearson Correlation Coefficient (0.69) is higher than the value of the Standard Error (0.04) multiplied by the Student T with 00 degnies of freedom (1645).